(untitled) (Research, Society and Development, 2023)
Introduction: Leukemia is the accumulation of abnormal cells in the blood that replace normal cells, mainly white blood cell cells from an error in the DNA. Many studies have confirmed that prolonged hospitalization and procedures such as chemotherapy, radiotherapy, surgical treatment, significantly reduce the quality of life of children. Thus, physiotherapy aims to improve their quality of life, especially during chemotherapy treatment. Objective: To point out the benefits of pediatric physiotherapy in the treatment of children with leukemia. Methodology: This is an integrative literature review, through the analysis and study of articles published in indexed journals, between the years 2016 to 2022, with reference to the databases: Physical Therapy Evidence Database (PEDro), PubMed, and Scientific Electronic Library Online (SciELO). Results: After the searches, 15 articles were included, which demonstrate the benefits of aerobic, resistance and manual techniques in the treatment of children with leukemia. Conclusion: It was found in studies that, through exercises and physiotherapeutic techniques, children with leukemia can improve functionality, strength, cognition and physical resistance, also reducing the deleterious effects of psychosomatic chemotherapy such as fatigue, stress, depression and sleep disorder.